Borrowed words a history of loanwords in English - Durkin, Philip (Oxford University Press, 2014)
"The rich variety of the English vocabulary reflects the vast number of words it has taken from other languages. These range from Latin, Greek, Scandinavian, Celtic, French, Italian, Spanish, and Russian too, among others, Hebrew, Maori, Malay, Chinese, Hindi, Japanese, and Yiddish. Philip Durkin's full and accessible history reveals how, when, and why. He shows how to discover the origins of loanwords, when and why they were adopted, and what happens to them once they have been."--Publishers website.